THERAPEUTIC EFFECTS OF HUANGQI GUIZHI WUWU TANG COMBINED WITH LASER ACUPUNCTURE ON LOWER EXTREMITY PERIPHERAL NEUROPATHY CAUSED BY TYPE 2 DIABETES FROM THE PERSPECTIVE OF TRADITIONAL MEDICINE MODERNIZATION (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the mechanisms of action of Huangqi guizhi wuwu tang and laser acupuncture from the perspective of modernizing traditional medicine, in order to provide a scientific basis and potential clinical application of this method in treating peripheral neuropathy complications of type 2 diabetes.Method: This study evaluated the efficacy of Huangqi guizhi wuwu tang combined with laser acupuncture in the treatment of lower extremity peripheral neuropathy caused by type 2 diabetes with a pattern of qi deficiency and blood stasis, conducted on 80 patients over a 21-day course.Results: The combination of Huangqi guizhi wuwu tang and laser acupuncture has shown significant effectiveness in improving clinical symptoms of pain, numbness, and paresthesia, enhanced quality of life, supported blood glucose control, and promoted recovery and enhancement of nerve conduction velocity. From the perspective of modern research, the therapeutic effects of this integrative approach can be explained as follows: the herbal components of Huangqi guizhi wuwu tang have been shown to modulate oxidative stress, facilitate the repair of damaged nerve fibers, and balance intracellular glucose metabolism. Laser acupuncture exerts analgesic, anti-inflammatory, circulatory-enhancing, endocrine-regulating, and neuroprotective effects.Conclusion: The combination of Huangqi guizhi wuwu tang with laser acupuncture improves clinical manifestations and provides supportive therapeutic and preventive benefits for complications, particularly lower extremity peripheral neuropathy caused by type 2 diabetes.
Keywords: Huangqi guizhi wuwu tang, laser acupuncture, lower extremity peripheral neuropathy, type 2 diabetes, traditional medicine.